The Routledge handbook of global perspectives on homelessness, law & policy - Bevan, Chris (Routledge, 2024)
"This handbook provides a comprehensive global survey and assessment of the law and policy relating to homelessness prevention. Homelessness is regarded internationally as one of the most pressing issues facing humanity and one of the greatest social challenges of our times. This has been further amplified as a result of the Covid-19 pandemic. Across the globe, there is an enormous divergence in both experiences of and responses to homelessness from governments and state actors. This handbook examines how different jurisdictions from across all five continents of the world have encountered, framed and responded to homelessness. Written by expert scholars and leaders in their field, the book engages in a multidisciplinary and comparative analysis of homelessness as an issue of acute social concern. Understandings of homelessness are geographically, culturally and historically situated, making analysis of each jurisdiction's approach by a national expert deeply insightful. The collection examines legal and extra-legal policy interventions targeted at reducing or preventing homelessness from across the globe. Drawing on diverse perspectives, differing cultures and welfare regimes, it thus constitutes a timely evaluation of current approaches to homelessness internationally. This book will appeal to students and scholars of homelessness, sociology, social policy, anthropology, and urban sociology, as well as international and national policy-makers"--